Efficacy of ALA-PDT for epidermoid cyst on the face: A retrospective study - Haiyan Zhang; Yu Yan; Yan Zhao; Zhongxia Zhou; Jiawen Gao; Ronald Sroka; Linglin Zhang; Xiuli Wang (Photodiagnosis and Photodynamic Therapy)
Background: Epidermoid cysts are usually single, benign, keratin-filled cysts which occur mainly on the face and upper trunk of young adults. Surgical resection is the main treatment, which inevitably leaves scars and may recur. Photodynamic therapy (PDT) has been reported as a non-invasive and promising treatment for various skin diseases with cosmetic benefits.Methods: 14 patients with single epidermoid cyst located on the face received ALA-PDT treatment. After the plum-blossom needle pretreatment, cyst was incubated with 5 % ALA cream for 30 min and then irradiated with 633 nm LED red light. If complete remission wasn’t achieved after one session of ALA-PDT treatment, more sessions would be repeated once every 1–2 weeks. Follow-ups were conducted every 2 weeks after the end of treatment.Results: All patients achieved complete regression of cyst after 1 to 3 ALA-PDT sessions. None of the patients experienced recurrence or scarring during the follow-up period (0.5 to 28months). Mild adverse effects were observed, including transient pain, erythema, and edema.Conclusion: In this observational study, ALA-PDT showed good efficacy and mild adverse reactions, suggesting that ALA-PDT is a promising treatment for epidermoid cysts on the face with cosmetic benefits.